Perioperative Mobile Telehealth Program for Post-Prostatectomy Incontinence: A Randomized Clinical Trial. Issue 2 (7th August 2022) - Goode, Patricia S.; Johnson, Theodore M.; Newman, Diane K.; Vaughan, Camille P.; Echt, Katharina V.; Markland, Alayne D.; Kennedy, Richard; Van Arsdalen, Keith N.; Rais-Bahrami, Soroush; Issa, Muta M.; Barnacastle, Susan; Wright, Kate Clark; et al.
Abstract : Purpose: Perioperative pelvic floor muscle training can hasten recovery of bladder control and reduce severity of urinary incontinence following radical prostatectomy. Nevertheless, most men undergoing prostatectomy do not receive this training. The purpose of this trial was to test the effectiveness of interactive mobile telehealth (mHealth) to deliver an evidence-based perioperative behavioral training program for post-prostatectomy incontinence. Materials and Methods: This was a 3-site, 2-arm, randomized trial (2014–2019). Men with prostate cancer scheduled to undergo radical prostatectomy were randomized to a perioperative behavioral program (education, pelvic floor muscle training, progressive exercises, bladder control techniques) or a general prostate cancer education control condition, both delivered by mHealth for 1–4 weeks preoperatively and 8 weeks postoperatively. The primary outcome was time to continence following surgery measured by the ICIQ (International Consultation on Incontinence Questionnaire) Short-Form. Secondary outcomes measured at 6, 9 and 12 months included Urinary Incontinence Subscale of Expanded Prostate Cancer Index Composite; pad use; International Prostate Symptom Score QoL Question and Global Perception of Improvement. Results: A total of 245 men (ages 42–78 years; mean=61.7) were randomized. Survival analysis using the Kaplan-Meier estimate showed no statistically significant between-group differences in time to continence. Analyses at 6 months indicated no statistically significant between-group differences in ICIQ scores (mean=7.1 vs 7.0, p=0.7) or other secondary outcomes. Conclusions: mHealth delivery of a perioperative program to reduce post-prostatectomy incontinence was not more effective than an mHealth education program. More research is needed to assess whether perioperative mHealth programs can be a helpful addition to standard prostate cancer care.